2011
DOI: 10.1115/1.4003310
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stresses Remain Elevated in Mature Arteriovenous Fistulas: A Case Study

Abstract: Maintaining vascular access (VA) patency continues to be the greatest challenge for dialysis patients. VA dysfunction, primarily due to venous neointimal hyperplasia development and stenotic lesion formation, is mainly attributed to complex hemodynamics within the arteriovenous fistula (AVF). The effect of VA creation and the subsequent geometrical remodeling on the hemodynamics and shear forces within a mature patient-specific AVF is investigated. A 3D reconstructed geometry of a healthy vein and a fully matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
2
36
2
Order By: Relevance
“…Although it is generally accepted that the vessel remodeling after fistula creation is a process of mechanical homeostasis [9], increasing evidence is questioning the traditional view that there is a complete restoration of a normal homeostatic shear stress at the end of the normal maturation process [13,30]. Instead, it has been suggested that there is only a partial restoration of homeostatic shear stress [31].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Although it is generally accepted that the vessel remodeling after fistula creation is a process of mechanical homeostasis [9], increasing evidence is questioning the traditional view that there is a complete restoration of a normal homeostatic shear stress at the end of the normal maturation process [13,30]. Instead, it has been suggested that there is only a partial restoration of homeostatic shear stress [31].…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested by Carroll et al [13] that high shear (exceeding 15-20 Pa) can initiate aggressive intimal hyperplasia and patency threatening stenoses, based on computational observations that high shear in stenosis-free vessels is localized at sites which are generally prone to lesion formation. It was hypothesized in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the upstream events that may contribute to neointimal hyperplasia formation, the hemodynamic shear stress at the AVF anastomosis was investigated in several CFD studies in the last decade (40)(41)(42)(43). Numerical analysis of flow velocity has been validated with established experimental data (44), even for high values of the Reynolds number, an index of flow instability or turbulence.…”
Section: Disturbed Flow Patterns In the Avfmentioning
confidence: 99%